Penilaian otentik kemampuan berpikir kritis matematis siswa SMP Kelas VIII pada materi statistika - Wijayanti, Ardhina; Nursaadah, Ida; Faslurrohman, Muhammad; Muna, Khozainul; Rohmah, Ulya Shofirotur; Dewanti, Sintha Sih (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2024)
Mathematical critical thinking is essential for students in the twenty-first century. People become more adaptive, open-minded, and better able to react to a range of events and problems as their critical thinking skills grow. The ability for children to think critically is still quite limited. The lack of instruction that fosters mathematical critical thinking skills is to blame for this. After giving students a mathematical critical thinking stimulus while they were studying, this study aims to assess students' capacity to use critical math thinking on statistical content. The research technique used is called qualitative descriptive research. Data collection techniques include test-and-nontest approaches. Analysis of critical thinking skills is done by looking at assessment, assumption analysis, and argument analysis. Students from SMP Negeri 9 Yogyakarta in grade VIII made up the research sample. This research produces three categories of students' critical thinking abilities, namely: 1) high category students are able to analyze assumptions, analyze arguments, and evaluate; 2) medium category students are able to analyze arguments and evaluate, but are still not capable enough to analyze assumptions; and 3) low category students are not yet able to analyze assumptions, analyze arguments, and evaluate.